Motility as a mediating variable in the influence of environmental concern on mobility habits - Alexis Gumy; Eloi Bernier; Guillaume Drevon; Vincent Kaufmann; Thomas Buhler (Journal of Urban Mobility)
This study employs a second-order structural model (SEM) to conduct a mediation analysis, with the objective of elucidating the intricate relationship between environmental concerns and daily mobility habits. The mediation variable used is motility, defined as the personal capacity to be mobile, and combines individuals’ access, skills, and projects related to the transportation system. This study utilizes data from the second wave of the ‘National daily mobility panel’ (2019, ELIPSS) survey in France to demonstrate that higher environmental concern may lead to stronger public transportation habits and less frequent car use. However, the relationship between these variables is not straightforward but rather significantly contingent upon the unequal distribution of motility among the population. Among lower education or income groups, the lack of motility can impede the translation of environmental concern into mode shift. These findings contribute to the identification of more seamless and less standardized strategies for a transition towards socially and environmentally sustainable daily mobility habits.